Аналіз експериментальної статистики інтервалів. 1. Еквівалентність статистики інтервалів і статистики відліків - Кучмагра, О.А.; Одинокін, Г.І.; Скорбун, А.Д.; Стадник, С.М. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
Представлено результати експериментальної перевірки еквівалентності статистики довгих рядів інтервалів між моментами реєстрації нейтронів і статистики отриманих з них відліків блока детектування нейтронного потоку й наведено числову оцінку такої еквівалентності. Розрахункові значення для експериментальних даних порівнювалися з відповідними значеннями, отриманими з модельних даних. В якості модельних даних використовувалася вибірка чисел, розподілених за експоненціальним законом, отримана за допомогою генератора випадкових чисел. Обсяг модельної вибірки і середнє значення відповідали експериментальним даним. Представлены результаты экспериментальной проверки эквивалентности статистики длинных рядов интервалов между моментами регистрации нейтронов и статистики полученного из них количества отсчетов блока детектирования нейтронного потока и дается числовая оценка такой эквивалентности. Расчетные значения для экспериментальных данных сравниваются с соответствующими значениями, полученными из модельных данных. В качестве модельных данных использовалась выборка чисел, распределенных по экспоненциальному закону, полученная с помощью генератора случайных чисел. Объем модельной выборки и среднее значение соответсвуют экспериментальным данным. The results of experimental checking of equivalence for long sets of intervals statistics between moments of neutrons registration, and statistics of received from them count rates from a detecting block are given. A numerical evaluation of such equivalence is given. Calculated values for experimental data were compared with the corresponding ones, which were received from the model data. As a model data, the sample of numbers which are distributed according to an exponential law, have been used. The volume and mean value of the model data were the same as in experimental ones. The statistical parameters studied were the ratio of the mean square deviation to the mean for the intervals, and the ratio of the variance to the mean for the count rate, that is, respectively for the exponential and Poisson distributions. The theoretical values of these ratios are known and equal to unity. It is shown that when calculating the number of samples from the experimentally measured sample of time intervals in order to obtain a satisfactory uncertainty of the statistical parameters, the exposure time Δ, for which the number of counts is counted, must be in a certain range from Δmin to Δmax, which depend on the mean interval value.